Implementation of Artificial Intelligence-Based Instructional Media in Islamic Religious Education: A Case Study at SMP Negeri 4 Muara Bungo - Ahmad Alvan Faiz Nuthgi Fadli; Andryadi; Dedi Yuisman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The increasing adoption of Artificial Intelligence (AI) in education has transformed instructional practices by enabling more adaptive and interactive learning environments. However, the utilization of AI in Islamic Religious Education (PAI) remains relatively limited, particularly in regional schools with restricted technological readiness and digital literacy. This study aimed to explore the utilization of Artificial Intelligence (AI) in developing instructional media for Islamic Religious Education at SMP Negeri 4 Muara Bungo, including the challenges encountered and the adaptive strategies implemented by teachers during the integration process. This study employed a qualitative descriptive-exploratory design involving two PAI teachers and thirty students selected through purposive sampling. Data were collected through observations, interviews, and documentation and analyzed using Miles and Huberman’s interactive analysis model. The findings revealed that teachers utilized AI-based applications such as ChatGPT, Canva AI, and Gamma AI to develop instructional materials and interactive learning media. The integration of AI contributed positively to instructional efficiency, increased students’ engagement, and created more interactive classroom learning experiences. Nevertheless, teachers encountered several challenges, including limited digital literacy, technological infrastructure barriers, and concerns regarding the reliability of AI-generated information. To optimize AI utilization, teachers adopted several adaptive strategies, including self-directed learning, collaborative adaptation, and the integration of AI-supported media with conventional instructional approaches. This study provides empirical evidence regarding AI utilization in Islamic Religious Education within regional school contexts while emphasizing the importance of balancing technological innovation with pedagogical and moral values.